2015 17th International Conference on Transparent Optical Networks (ICTON) 2015
DOI: 10.1109/icton.2015.7193316
|View full text |Cite
|
Sign up to set email alerts
|

Photonic biosensor chip for early-stage cancer diagnosis

Abstract: This paper introduces a general design of a silicon wire "lab on a chip" photonic biosensor for medical diagnosis application, especially for early-stage cancer diagnosis. The sensitivity of detection of the biosensors developed is at least 10-100 times more sensitive than that of current commercial biosensors. KeywordsSilicon wire evanescent field biosensor; "Lab on a chip"; cancer early-stage diagnosis; sensitivity of detection; label-free detection; real time detection; multi-analytes' parallel detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This device can be further improved by reducing the silicon core thickness from 0.32 µm to 0.22 µm which will greatly reduce the footprint of the MMI and will be more suitable for standard SOI fabrication. By using narrow single mode input and output waveguides and connecting N individual Mach-Zehnder interferometers to the outputs, this device can be used for evanescent field biosensing applications [18,26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This device can be further improved by reducing the silicon core thickness from 0.32 µm to 0.22 µm which will greatly reduce the footprint of the MMI and will be more suitable for standard SOI fabrication. By using narrow single mode input and output waveguides and connecting N individual Mach-Zehnder interferometers to the outputs, this device can be used for evanescent field biosensing applications [18,26].…”
Section: Discussionmentioning
confidence: 99%
“…Although MMI splitters are widely used in telecommunication, the devices presented in this paper are developed for biosensors to enable parallel detection and identification of multiple analytes in multiple samples with extremely high sensitivity of detection [18]. This is achieved by connecting a Mach-Zehnder Interferometer (MZI) via S-bends to each output of the MMI splitter.…”
Section: Introductionmentioning
confidence: 99%
“…This progress is particularly significant in early diagnosis as <20 percent of ovarian cancer can be diagnosed in the early stages [134]. A photonic biosensor based on the silicon "lab-on-achip" for early-stage cancer has shown a sensitivity of at least 10 to 100 times greater than that of current commercial biosensors [135]. Shafiee et al have demonstrated a mechanism free of etiquette optical sensing by nanostructured photonic crystals (PC).…”
Section: Literature Overview (State Of the Art)mentioning
confidence: 99%
“…Assim, uma variedade de dispositivos têm sido desenvolvidos nesta plataforma, sendo avaliados a sua largura de banda, qualidade, compatibilidade com processos de fabricação conhecidos e facilidade no encapsulamento. O desenvolvimento de diferentes dispositivos nanofotônicos para telecomunicações como moduladores e divisores de polarização [5][6][7][8], é uma amostra do atual momento no qual a tecnologia fotônica se encontra em um amplo processo de desenvolvimento, além de uma grande variedade de outras aplicações industriais [9][10][11].…”
Section: Contexto De Pesquisaunclassified